Web-Based Online Information System Model: One way to increasing the financial inclusion of MSMEs during the Covid-19 Pandemic (Case Study of MSMEs in Blitar) (International Conference of Graduate School on Sustainability (ICGSS), 2020)
During  the Covid-19 pandemic  made human interactions and activities reduced, this also had an impact on all business sectors, especially MSMEs. The government identified four main problems  by micro, small and medium enterprises (MSMEs) during the Covid-19 pandemic, namely decreased demand, product marketing, access to raw materials and still low human resources, and the main problem is the decline in demand. To support MSMEs survive, the government has provided various incentive and stimulus facilities, including interest subsidies, placement of government funds in commercial banks for credit restructuring, spending on guarantee services, guarantees for working capital, investment financing to cooperatives through the LPDB-Ministry of Cooperatives and SMEs , and MSMEs  final income tax incentives. Many opportunities for MSMEs to access credit from the government during this pandemic as well as the existence of a new normal to carry out an activity, including the obligation to wear masks and physical distancing, then the use of technology to increase the accessibility of banking products by MSMEs is needed.The research objective is to create a Web-Based Online Information System Model to increase the financial inclusion of MSMEs during the Covid-19 Pandemic and it is hoped that with an increase in financial inclusion, MSMEs can survive during the Covid-19 pandemic. This research is a descriptive study and applied research. The units of analysis are 1) MSMEs 2) Banking and 3) Department of Cooperatives and MSMEs. The sampling technique was based on purposive sampling. The data analysis technique uses descriptive analysis to describe the findings and policies that involve interested parties to create a web-based online information system model to increase the financial inclusion of MSMEs during the Covid-19 Pandemic.In the web-based online information system, there are 3 users, namely MSMEs, Banking and the Office of Cooperatives and MSMEs. The  Office of Cooperatives and MSMEs is in control of this model, to log in to this system, MSMEs and Banks must create a user login via the Office of Cooperatives and MSMEs. The function of banking in this model is to provide information on banking products that can be accessed by MSMEs, accompanied by information about the requirements for applying for credit. The last user is MSMEs, when MSMEs apply for credit, the Cooperative Office will verify the existence and business of MSMEs, then if according to the Cooperative Office it is feasible to apply for credit, then MSMEs are welcome to complete and input all credit requirements required by the intended bank. The Cooperative Office then forwards the credit application file to the intended bank, then the bank verifies if there is a file that is not enough for MSMEs to be able to revise it. All information, whether from MSMEs to Banking or  from Banking to MSMEs, is always through the Cooperative Office. In the end, if the completeness of the credit is complete and approved by the bank, the credit can be disbursed.